The Study of Demented Patients Who Showed Intellectual Improvement After Admission to a Hospital where they Could be Given Special Therapy for Dementia - Endo, Hidetoshi; Yamamoto, Takayuki; Kono, Kazuhiko; Kuzuya, Fumio (Nippon Ronen Igakkai Zasshi. Japanese Journal of Geriatrics, 1989)
The authors evaluated the changes in the scores on Hasegawa's rating scale for dementia (HRSD) of demented patients in a hospital for dementia. The subjects in this study were 69 patients (12 males and 57 females) including 34 with dementia of the Alzheimer type (DAT), 30 with multi-infarct dementia (MID) and 5 with mixed dementia. Their average age was 75.6 years and the mean period after symptom onset was 2.5 years. The observation period was 5 months after admission to the hospital. We rated HRSD on admission and each month after admission. During the observation period, 65 patients received drugs orally and 65 patients were given rehabilitation for impaired cerebral function. We tried to classify the pattern of change in the HRSD into 5 groups as follows; 1) no remarkable change or deterioration, 2) wavering, 3) improvement during only the first month, 4) improvement from the first month after admission, 5) improvement from admission. We assumed that the patients in group 3) had been underestimated on admission. Their mental states might have been confused on admission because of the change in their living environment. Thus we rejected this group for statistical analysis and compared the madical characteristics of those in the non-improved group (1 and 2) with those in the improved group (4 and 5). The period from onset of symptoms in the improved group was shorter than in the non-improved group (p<0.05). Moreover there was a tendency (p<0.1) toward less abnormal findings in the EEG and less cerebral atrophy on CT scan in the improved group. Indeed, many DAT cases who were thought to be resistant to therapy were included in the improved group. These results indicate the necessity of admission for therapy of dementia at an early stage, the importance of adequate care by well-trained staff and a good environment in which patients can receive psychorehabilitation.